Students' Islamic personality on ibada: A structural equation model - Ismail, Nik Ahmad Hisham; Tekke, Mustafa; Othman, Nooraini; Abd Razak Al-Hafiz, Afareez (Elsevier, 2016)
The aim of the study is to examine the factorial structure of Ummatic Personality Inventory.The sample of the study is a group of female stuedents (n=289) in government schools.Data was analysed using CFA and SEM. The findings of the SEM indicates that Fardhu Ain correlated to Fardhu Kifayah. Thus more efforts should be put to educate students with Fardhu Ain.